2008
DOI: 10.1111/j.1468-3083.2008.02590.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastases from different internal malignancies: a clinical and prognostic appraisal

Abstract: The risk of skin metastases depends largely on the characteristics of tumour cells, which is similar among different ethnic groups. In terms of prognosis, a subset of breast cancer patients has superior prognosis, even among breast cancer patients with stage IV disease. Physicians should consider this finding in clinical situations to avoid possible misinformation about the prognosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
157
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(176 citation statements)
references
References 31 publications
(54 reference statements)
12
157
3
4
Order By: Relevance
“…The most common presentation of a metastatic skin lesion is a firm, painless nodule (multiple nodules are found in 46.4% of patients and a single nodule in 37.7% of patients; these can be macules, plaques, erythematous plaques, and ulcers). 3 Previous reports indicate that the most common presentation of cutaneous metastases of cholangiocarcinoma is the nodular type; other skin lesions described include erythematous plaques, abscesses, and ulcers. [4][5][6][7][8][9][10][11] Most nodular lesions are firm, painless, and nonulcerative and covered by a normal appearing epithelium; this results in some lesions being misdiagnosed as benign.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common presentation of a metastatic skin lesion is a firm, painless nodule (multiple nodules are found in 46.4% of patients and a single nodule in 37.7% of patients; these can be macules, plaques, erythematous plaques, and ulcers). 3 Previous reports indicate that the most common presentation of cutaneous metastases of cholangiocarcinoma is the nodular type; other skin lesions described include erythematous plaques, abscesses, and ulcers. [4][5][6][7][8][9][10][11] Most nodular lesions are firm, painless, and nonulcerative and covered by a normal appearing epithelium; this results in some lesions being misdiagnosed as benign.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al 3 reported that the majority of patients (73.8%) with skin metastases had concomitant visceral metastases at the time of, or following cutaneous presentation. The two previously reported patients who presented with cutaneous metastases of cholangiocarcinoma, as well as the two patients described here, all died within 7 months of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CM lesions are usually multiple and may range from 1 to 100. [7] In our study only one patient of because normally cutaneous metastasis occurs in later stages of disease when it has become widely disseminated in the lymphohaematogenous route. Skin-coloured to erythematous nodules at multiple sites were the most common clinical presentation of cutaneous metastases seen in 57.1% patients.…”
Section: Discussionmentioning
confidence: 99%